PERAN SERTA RUMAH SAKIT SWASTA DALAM PROGRAM KESEHATAN IBU DAN ANAK STUDI KASUS DI RUMAH SAKIT ISLAM YOGYAKARTA PDHI - Widodo Wirawan; Mubasysyir Hasanbasri; Mohammad Hakimi (Jurnal Kebijakan Kesehatan Indonesia, 2015)
ABSTRACT Background: Government limitations in the implementation of health care becomes an obstacle to modify individual factors in utilizing community MCH services. The private setor, such as private hospitals, has their own role in MCH services. This role can not be ignored because the number of private hospitals is more than the number of public hospital and the growth is also faster.. Objectives: This study was conducted to explore and understand the participation of the private hospitals in the government’s MCH program through case studies in Yogyakarta Islamic Hospital PDHI, and exploring the feasibility of private hospitals as a service provider of the MCH program.. Method: The study used a qualitative method with case study design. The variables measured were the resources, participation, barriers and challenges, as well as the strategic value. Data is collected through in-depth interviews to respondents from PDHI Foundation board, directors, manager, medical staffs, and the patient or their family, as well as field observations, and document tracking. Result: Private hospital has a major role in government MCH program through MCH services its self, facilities and infrastructure, and resources doctors and paramedics. Private hospitals encountered the obstacles in implementing MCH programs, such as the amount of government insurance payments that are not in accordance with the cost of private hospital services and there is tariff discrimination based on hospital class. The government also is not optimal in socializing MCH program guideline in private hospitals, while the referral systems between health facilities are still not smooth. Conclusion: The participation of the private hospitals in the MCH program is not optimal, influenced by financing for MCH programs, weak referral systems, and government lack of facilitation for the infrastructure development and medical personnel, and lack of socialization MCH program guideline